Differentiating Ventricular From Supraventricular Arrhythmias Using the Postpacing Interval After Failed Antitachycardia Pacing. (April 2018) - Bennett, Matthew T.; Leader, Nathan; Sapp, John; Parkash, Ratika; Gardner, Martin; Healey, Jeffrey S.; Thibault, Bernard; Sterns, Larry; Essebag, Vidal; Birnie, David; Sivakumaran, Soori; Nery, Pablo; et al.
Abstract : Background: Implantable cardioverter defibrillator arrhythmia discrimination algorithms often are unable to discriminate ventricular from supraventricular arrhythmias. We sought to evaluate whether the response to antitachycardia pacing (ATP) in patients with an implantable cardioverter defibrillator could further discriminate ventricular from supraventricular arrhythmias in patients receiving ATP. Methods and Results: All episodes of ventricular or supraventricular tachycardia where ATP was delivered in patients enrolled in RAFT (Cardiac-Resynchronization Therapy for Mild-to-Moderate Heart Failure Trial) were included. RAFT randomized 1798 patients with New York Heart Association class II/III heart failure, left ventricular ejection fraction ⩽30%, and QRS duration of ≥120 ms to a implantable cardioverter defibrillator±cardiac resynchronization therapy. The tachycardia cycle lengths (TCLs) before and after the delivery of ATP and the postpacing intervals were assessed. Overall, 10 916 ATP attempts were reviewed for 8150 tachycardia episodes in 924 patients. After excluding tachycardias where ATP terminated the episode or where the specific mechanism of the tachycardia was uncertain, we analyzed 3676 ATP attempts delivered for 2046 tachycardia episodes in 541 patients. A shorter difference between postpacing interval and TCL (PPI−TCL) was more likely to be associated with ventricular tachycardia than with supraventricular tachyarrhythmia (138.1±104.2 versus 277.4±126.9 ms; p <0.001). Analysis of the receiver operator curve for the PPI−TCL revealed an area under the curve of 0.803 ( p <0.001; 95% confidence interval, 0.784–0.822). The majority of tachycardias with a PPI−TCL >360 ms were supraventricular with a PPI−TCL value of ⩽360 ms having a sensitivity of 97.4% and specificity of 28.3% for ventricular tachycardia. Conclusions: The ATP response, specifically the PPI−TCL, can further discriminate ventricular from supraventricular arrhythmias in patients with implantable cardioverter defibrillators when the currently available discriminators fail. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00251251. Abstract : Supplemental Digital Content is available in the text.